2006
DOI: 10.1590/s1678-77572006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Dental mineralization and salivary activity are reduced in offspring of spontaneously hypertensive rats (SHR)

Abstract: Several pathologies have been diagnosed in children of hypertensive mothers; however, some studies that evaluated the alterations in their oral health are not conclusive. This study analyzed the salivary gland activity and dental mineralization of offsprings of spontaneously hypertensive rats (SHR). Thirty-day-old SHR males and Wistar rats were studied. The salivary flow was evaluated by injection of pilocarpine, the protein concentration and salivary amylase activity, by the Lowry method and kinetic method at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(26 reference statements)
1
6
0
1
Order By: Relevance
“…38 Hypertension can also be associated with a high susceptibility to the development of pathologies that impair oral health, which can decrease salivary flow and protein concentration of saliva. Elias et al 39 found that salivary flow and average concentration of proteins in saliva were reduced, but with no changes in salivary amylase activity in hypertensive cases. Additionally, the authors also observed, by means of microhardness analysis, that teeth of hypertensive rats have lower enamel and dentin resistance.…”
Section: Relationship Between Hypertension and Oral Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Hypertension can also be associated with a high susceptibility to the development of pathologies that impair oral health, which can decrease salivary flow and protein concentration of saliva. Elias et al 39 found that salivary flow and average concentration of proteins in saliva were reduced, but with no changes in salivary amylase activity in hypertensive cases. Additionally, the authors also observed, by means of microhardness analysis, that teeth of hypertensive rats have lower enamel and dentin resistance.…”
Section: Relationship Between Hypertension and Oral Health Problemsmentioning
confidence: 99%
“…Additionally, the authors also observed, by means of microhardness analysis, that teeth of hypertensive rats have lower enamel and dentin resistance. 39 Furthermore, Inoue et al 40 suggested that the mechanism of mineralization in hypertensive rats is abnormal, given that their trabecular bone presented a lower mineral state in both young and adult rats.…”
Section: Relationship Between Hypertension and Oral Health Problemsmentioning
confidence: 99%
“…2 In animals, the male offspring (30 days old) of spontaneously hypertensive rats (SHR) have mandibular incisor teeth with decreased enamel and dentin hardness as compared to the male offspring of normotensive Wistar rats. 3 Poor mineralization of these dental structures might favor the condition described as Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. amelogenesis imperfecta, which is observed in the teeth of Stroke-prone SHR (SHRSP).…”
Section: Introductionmentioning
confidence: 99%
“…18,19,20,21,22 Few studies can be found correlating endodontic disease and hypertension. Allareddy et al, 23 conducted a retrospective study where they found that 24.6% of patients hospitalized for periapical abscesses were hypertensive.…”
mentioning
confidence: 99%